P-278 Serum Levels of Lipopolysaccharides and CD26 in Patients with Crohn's Disease. (February 2017) - Magro, Daniela; Kotze, Paulo; Camargo, Michel; Carlos, Martinez A.; Guadagnini, Dioze; Antonio, Calixto; Vasques Ana, Carolina; Geloneze, Bruno; Pareja, José; Ayrizono, Maria de Lourdes; Saad, José M.; Coy, Claudio
Abstract : Background: Lipopolysaccharides (LPS) is a molecule formed by lipids and polysaccharides, the major cell wall component of Gram-negative bacteria. It is speculated that LPS may be associated with the inflammation in Crohn's disease (CD). High LPS levels are also known, by means of TLR-4 activation, to block CD26 expression. The aim of this study was to determine the serum levels of LPS and CD26 in CD subjects and correlate them with C-reactive protein (CRP), interleukins, CDAI, and TNF-α serum levels. Methods: We analyzed the levels of LPS, CD26 and correlated them with TNF-α, IL-1β, IL-6, IL-17, and CRP levels in 27 individuals (10 with active CD, 10 with inactive CD and 7 controls). The variables were also correlated with the Crohn's disease activity index (CDAI). Results: Serum levels of LPS were significantly elevated in active CD group ( P = 0.004). IL-1β ( P = 0.002), IL-6 ( P = 0.003), and IL-17 ( P = 0.000) were lower in the CD groups. Serum TNF-α was increased in the active CD group. The CRP levels were elevated in the CD groups when compared to controls ( P < 0.01). The CD26 levels in the CD groups were lower than in the control group ( P = 0.000). There were no correlation between LPS and CD26 with CRP, interleukins and TNF-α. Conclusions: Individuals with CD presented higher serum levels of LPS, with an increase varying from 2 through 6-fold, depending on disease activity when compared with healthy controls and CD26 levels were lower in the CD groups. Both LPS and CD26 correlated with the severity of the disease and are highlighted as biomarker of CD. Future implications of these findings could correlate these molecules to the inflammatory status of CD, and need to be better studied. FAPESP process 2014/06164-8